Qualitative Phytochemical Screening and Antioxidant Properties of the Leaves of Miconia crenata (Vahl) Michelang. (Melastomataceae) from Ayer Hitam Utara Forest Reserve, Johor, Malaysia - Salasiah Mohamad; Nur Adila Jamil; Cuevas Linatoc, Alona; Muhamad Sa'ed, Mohamad Ifratshim (Journal of Sustainable Natural Resources, 2024)
Medicinal plants have long been recognised as valuable resources for traditional medicine and modern pharmaceutical research due to their rich reservoirs of bioactive compounds. This research aims to provide data on the phytochemical content and antioxidant activity of a common tropical shrub, Miconia crenata, from Ayer Hitam Utara Forest Reserve. Total flavonoid content was determined by using the chloride colorimetric method, while antioxidant activity was validated by the DPPH radical scavenging assay. Phytochemical screening of M. crenata revealed secondary metabolites such as phenols and flavonoids, while the methanol extract of the leaves of M. crenata showed a total flavonoid content of 508.84 ± 154.42 mg/mg at a concentration of 0.02 mg/mL, and antioxidant activity recorded a low IC50 value of 40.54 ?g/mL, indicating a high antioxidant potential.